From corporate social responsibility to consumer responsibility: a study of the factors that influence purchase intentions - Savolainen, Joonas (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
There is increasing evidence that consumers expect companies to behave in a sustainable manner. While managers are beginning to acknowledge this demand, they are sometimes faced with a frustrating situation where sustainable actions on the company’s part do not translate into profits. This may be due to the fact that a relatively small percentage of consumers are actually willing to behave according to their pro-sustainability attitudes. Therefore, the purpose of this study is to examine which factors most influence consumers’ responsible purchase intentions. This study uses quantitative methods to examine how the perceived importance of CSR, personal responsibility for sustainability and price and quality affect consumers’ purchase intentions. For this purpose, a framework was built using existing literature on corporate social responsibility, consumer responsibility and factors that affect responsible purchase intentions. Empirical data was collected through a survey questionnaire that was distributed to Finnish speaking students at the Turku School of Economics. The data was then analyzed using logistic regression. The results confirm previous findings on the positive influence of the perceived importance of CSR. Similarly, the study confirms that personal responsibility for sustainability is a strong predictor of responsible purchase intentions. Conversely, the high price of ethical goods acts as a deterrent against responsible shopping. In addition to affirming these relationships, the study also measured the potential influence that various reference groups and other actors have on consumers’ responsible behavior. Surprisingly, companies figured among the top influencers. This implies that companies could actually do a great deal more to promote sustainability matters than they are doing today. Acting together with suppliers and other partners, they could participate in making consumers more responsible. This would also promote the use of sustainable products and more importantly would act as catalyst for a greater change in sustainable living and consumption.